The God of War and his Prince of Peace - Theron, PF (Nederduitse Gereformeerde Teologiese Tydskrif, 2004)
We are confronted with the fact that religion (including the Christian religion) and violence are apparently closely connected. At the same time religion (including the Christian religion) is historically intimately associated with peace. In the so-called “Song of the Sea” (Exodus 15) the God of Israel is celebrated as the “Lord of War” (vs 3), but on the other hand the Bible promises a Kingdom of everlasting peace brought about “not by might nor by power” but by the “Prince of Peace”? The pressing question put in this paper is whether the aggression of the God of war is compatible with the compassion of the Prince of peace, especially since the latter is claimed to be the revelation of the former.